O papel das Áreas de Proteção Ambiental (APAs) na conservação da biodiversidade brasileira - Magalhães, Daniel Rodrigo de Macêdo (2017)
Protected Areas are the main strategy to protected biodiversity. Protected Areas are not equal and vary in their management objectives and level of human occupation. Brazil has 12 protected area's categories. Among those, "Environment Protected Area" (EPA, Category V in IUCN Classification), is the one with least restriction to human activity. This category has many critics, that argue EPAs should not be account as Protected Areas, as has defenders who argue that EPA belong to a “New Paradigm” of Protected Areas, aimed to reconcile biodiversity conservation and human development. EPAs has special importance because it covers a third of the protected land, and more than 60% on biomes such as Atlantic Forest, Cerrado, Caatinga and Pampa, and more than 80% of all marine protected areas in Brazil. Therefore, understand the implementation, land cover and management patterns is crucial for Brazilian biodiversity conservation. We find lower levels of human activity within EPAs when compared with biome and in areas without protection (protected areas and indigenous areas) within biome. Nonetheless, we found about 7 million people live inside EPA and that in 2016, Amazon biome was the only biome with more than 50% of forest land cover. We find that if we do not account for the area with anthropogenic use inside EPA, the total area covered by protected area in Brazil would go from 17,6% to 12,8%. We also found that only 18% of EPA had a "management plan" and 45% had a "management council". Lastly, we recommend starting a discussion about specific management and support mechanism to the EPA category.